Optimum Antenna Height for 5G Radio Networks Using the Spatial Multi-tier Microcell Method - Mulyono, Mulyono; Oktaf B. Kharisma; Hasdi Radiles; Ahmad Faizal (JOURNAL OF INFORMATICS AND TELECOMMUNICATION ENGINEERING, 2025)
The construction of macrocell towers in large numbers has become a concern for city governments in terms of aesthetics. In 5G network technology, with a higher operating frequency, the resulting coverage becomes smaller, allowing for a reduction in antenna height. This study aims to re-evaluate the optimum antenna height based on coverage proportion criteria. Coverage calculations were performed using the COST 231 Hata path loss model and the Kathrein 742215 antenna model. A cellular network with a coverage radius of less than 500 m can utilize an antenna height of 10 m, where the required transmission power tends to be low, such as 1-watt, and a downtilt angle of 0° is sufficient. As the required cell radius increases beyond 500 m, the antenna height also becomes higher, starting from 20 m, with transmission power ranging from 10-watts to 20-watts and a downtilt angle in the range of 6°. Research findings also indicate that previous methods for calculating antenna height overlooked overshooting in the subsequent tier areas. Based on this method, coverage can be adjusted by considering handover zones and overshooting beyond the first tier